Numerical analysis of reinforced earth abutments - Ekli, Onur. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
This study is focused on numerical modeling of reinforced earth abutment walls with strip reinforcements as well as their working principles, elements, structural analysis techniques, and behaviour under seismic loads. Their advantages and disadvantages as well as their application on one real structure have been studied. The analysis of the real structure with superstructural and foundation engineering evaluations is also presented. The purpose of utilizing reinforced soil abutment walls instead of classical reinforced concrete structures is to make more economical and safe structures under the exposed loads and settlements experienced during the service life, especially in regions having high seismicity. Since they are more soil like structures, reinforced soil retaining walls can accommodate differential settlements and reduce earthquake response on the structural system. In order to exhibit the benefits of reinforced earth abutment walls, structural analysis are carried out with four different commercial programs ZARAUS, FLAC, and PLAXIS. For the considered case study of DDY-8 Railway Overpass Project in the content of “Bozüyük Mekece Improvement Project 2nd Part” their results are compared and critically evaluated. In flexible reinforced earth structures the deflection of the reinforced earth panels under the heavily concentrated loading of beam seats sometimes become the main concern of the clients. FLAC and PLAXIS are especially chosen, since they use different numerical methods, finite difference and finite elements respectively. Therefore they both have the ability to estimate the displacement values of the reinforced earth abutment structure. ZARAUS is used to verify the results by limit state analysis. Structural analysis results of the model study indicate that reinforced soil wall is a very beneficial structural solution as retaining structures of river banks, bridge abutments and retaining walls especially when incorporated with soft foundations and high seismicity.
Keywords: Retaining walls.